An Integrated Spatial Search Engine for Maps and Aerial Photographs on a Google Maps API Platform. Issue 2 (4th May 2017) - Ganor, Tamar
Abstract : A traditional library catalog does not do justice to maps and aerial photographs. Text can never fully describe them and maps' and aerial photographs' geographic coverage or perimeters cannot be displayed visually in the online public access catalog (OPAC), so searching based on their textual metadata without specific spatial reference data used also for display purposes is often not enough to locate relevant items. The Hebrew University of Jerusalem's (HUJI) Geography Department has developed a spatial search engine for their scanned aerial photographs collection that allows users to locate one or more aerial photographs according to the area of the Earth's surface that was photographed and their accompanying metadata. The Humanities and Social Sciences Library, which holds a large unscanned print map collection, has asked to integrate a similar map search mechanism in the Department's existing search engine, and a new website was launched in December 2015 (http://ccg.huji.ac.il/aerialphotos/ ) showing the aerial photographs' center points alongside the maps' rectangle perimeter. The search engine retrieves maps and aerial photographs that intersect with a user-drawn rectangle. This article discusses the characteristics of these collections, the rationale behind searching for maps and aerial photographs together, and the process of defining and building this spatial search engine. This method allows users to view which items are available in their area of interest side-by-side, on a Google Maps background map.